Trade, Transport and Tanda : Shifting Identities of the Banjaras - Choudhary, Manisha, (Brill | Manohar Publishers & Distributors, 2018)
The Banjaras were primarily a nomadic group. During the reign of Alauddin Khalji they were organized to collect grains from the country-side for smooth running of the market reforms. Later, they became an indispensable part of the Mughal economy and acquired a very important role as transporters for the empire and even continued with the same status under the East India Company. Banjaras were not only the suppliers, traders or transporters they also served as the commissariat for the Mughals and John Company. The main items they transported were non perishable goods mainly; grains and salt. Based on Chittiyat, Arzdasht and Arshatta documents archived at Rajasthan State Archives, Bikaner and travelogues, this volume focuses not only on the role and organization of Banjaras and Tanda but also on the shifting identity of Banjaras from nomadic to criminal over a period of time. The introduction of railways in India drastically changed the fate of these born transporters of the empire. The change of regime and the introduction of a new mode of transport led to the marginalization of the Banjaras and their practical elimination from the economic activities of the subcontinent.